2022
DOI: 10.1186/s12872-022-02498-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography: evaluating the effects of stent boost subtract imaging on stent underexpansion in STEMI patients

Abstract: Background To evaluate the effect of stent boost subtract (SBS) imaging on stent underexpansion during percutaneous coronary intervention (PCI) in patients with acute ST-segment elevation myocardial infarction (STEMI) by optical coherence tomography (OCT). Methods One hundred thirty-eight STEMI patients who underwent drug-eluting stent (DES) implantation were prospectively recruited and divided into the SBS group (69 cases) and the CAG group (69 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This difference mostly attributed to the larger percentage of cases needed pre-dilation that was not ideally performed (using small sized PTCA semi-compliant balloons, no use of 1:1 balloon to vessel size, no use of NC balloons; noting that 40% of our study cases needed pre-dilatation). Similarly, the current results were consistent with Yuanyuan Duan et al [ 18 ] as they found suboptimal results in 24% of STEMI cases (all study cases were acute MI, indicating more soft lesions that were stented). Also, Kang et al [ 28 ] found that 42% of cases during their study had stent under expansion by IVUS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference mostly attributed to the larger percentage of cases needed pre-dilation that was not ideally performed (using small sized PTCA semi-compliant balloons, no use of 1:1 balloon to vessel size, no use of NC balloons; noting that 40% of our study cases needed pre-dilatation). Similarly, the current results were consistent with Yuanyuan Duan et al [ 18 ] as they found suboptimal results in 24% of STEMI cases (all study cases were acute MI, indicating more soft lesions that were stented). Also, Kang et al [ 28 ] found that 42% of cases during their study had stent under expansion by IVUS.…”
Section: Discussionsupporting
confidence: 91%
“…The specificity of SB image for adequate stent deployment is high (100% when assessed by IVUS, and 96% when assessed by optical coherence tomography (OCT)), so it could be used as the first line for monitoring just after stent implantation in centres where IVUS is not routinely used. [ 17 , 18 ]. In our practice we do not use IVUS frequently for assessing the results of stent deployment, which is a major requirement that should be fulfilled.…”
Section: Introductionmentioning
confidence: 99%